Pola Konsumsi Natrium, Pola Tidur, Kebiasaan Merokok Dan Kejadian Hipertensi Pada Laki-Laki Dewasa Di Pesisir Pantai Kota Bengkulu - Mika, Xenia Revira; Jumiyati, Jumiyati; Yuliantini, Emy (JGK: Jurnal Gizi dan Kesehatan, 2024)
Background: Hypertension has the nickname the Silent Killer because it is deadly but is not accompanied by any previous symptoms. There are two risk factors for hypertension, namely risk factors that can be changed, namely sleep patterns, high sodium consumption, smoking, physical activity, stress, alcohol consumption and coffee consumption. Meanwhile, risk factors cannot be changed, namely age, gender, occupation, family history or heredity. Bengkulu Province Health Profile data for hypertension sufferers in 2018 reached 71,675 people. Meanwhile, data from the Bengkulu City Health Service from 20 community health centers, the fish market health center, is the number two incident of hypertension in men in 2019, reaching 180 cases (17.4%).Objective: This study aims to determine the description of sodium consumption patterns, sleep patterns, smoking habits and the incidence of hypertension in adult men in the Coastal Coastal Work Area of ​​the Bengkulu City Fish Market Health Center. Method : Cross sectional design, the variables studied were sodium consumption patterns, sleep patterns, smoking habits and the incidence of hypertension. The total sample of 46 respondents was taken using simple random sampling technique. Results: The results showed that adult men consumed more than 100.0% sodium category. Some respondents, 21.7%, experienced poor sleep patterns, 23 respondents, 50.0%, almost all were moderate smokers, and almost all 32.6% did not smoke. 43.5% had grade 1 hypertension and 30.4% had pre-hypertension. Conclusion : The incidence of hypertension in the Coastal Coast category is more than 100%.